El problema agrario en el Ecuador - Aguirre, Manuel Agustín (1973)
This article was scanned by the Aurelio Espinosa Polit Ecuadorian Library.In the Preincario, the ayllu or group of related families, intimately rooted to the land, is the agrarian economic cell. Collective ownership of the land, cultivation and consumption in common. In the absence of private ownership of the means of production, there was no division into classes or the State, which was the instrument of domination of the possessor class over the dispossessed.